Observatório Social de Maringá: as ações e os efeitos sobre a gestão pública - Mattiello, Kerla (2018)
The Social Observatory of Maringá (OSM) was created by a group of institutions in a postcorruption context in the city of Maringá, with the objective of effecting the participation of society in public management through the analysis of bidding processes and control in application of public resources. The purpose of this study was to understand the effects on public management of the actions taken by the Social Observatory of Maringá under the perspective of social accountability. To reach this objective, a qualitative approach was used, through a case study. The data were collected through the reports presented by the OSM, news, results of studies already done on the OSM and interviews. For the analysis, the data were organized in successive periods and the highlighted points were identified, these were analyzed. In order to analyze the actions of the OSM and its effects, theories of Organizational Learning were used to seek to measure the effects of the municipal government, New Public Management as a theory that explain the reforms of the State and influenced the design of Public Administration in Brazil and the Accountability, especially Social or Societal Accountability that is geared towards social control, initiated by citizens, local actors, civil society organizations, social movements and even through communication willing to participate and influence local public issues. As a result it was possible to identify the strategy of action of the OSM as participation through dialogue and the establishment of a relationship of trust with the public managers that allowed the creation of an institutionalized space of participation, with the cooperation of horizontal and of the press. The OSM's preventive approach can avoid the need for frequent use of accountability mechanisms, even if they are activated when necessary. These factors allowed to stimulate the responsiveness of municipal management and triggered a cultural change among the servers, produced improvements in the purchasing process and generated organizational learning, but not in a generalized way. The performance in daily administrative procedures and the need for technical knowledge and the need to control the actions developed by the OSM make it difficult to increase participation, even though the actions have popular support. In this way, it is also difficult to increase the responsiveness of public management.